Latent class analysis of aggression in martial arts and combat sports: A cross-sectional study - Cezary Kuśnierz; Marta Niewczas; Wojciech J. Cynarski; Grzegorz Bielec; Aleksandra M. Rogowska (PLoS ONE, 2025)
Previous research on aggression in martial arts and combat sports (MA&CS) has shown mixed results. Some studies showed that MA&CS training lowers aggression levels, while other studies found it increases aggression or has no effect. To explain better this inconsistency, this study used latent class analysis to identify distinct subgroups of MA&CS practitioners based on aggression levels and related demographic and sports factors. Previous research predominantly employed a variable-centered approach to investigate the relationships between variables and their impact on outcomes. This study adopts a person-centered approach to identify subgroups that exhibit similar patterns of aggression, thereby enhancing the understanding of individual differences through variable configurations. A cross-sectional study was conducted with 367 participants aged between 16 and 57 years old (M = 27.28, SD = 9.52), including 23% of women, and 76% MA&CS athletes in such disciplines as Brazilian jiu-jitsu (BJJ), karate Kyokushin (KK), mixed martial arts (MMA), and wrestling. Participants completed paper-and-pencil self-report psychological questionnaires, including the Buss-Perry Aggression Questionnaire and provided demographic information. Latent class analysis was performed using aggression scores, age, gender, education, economic status, MA&CS training experience, and discipline. Three latent classes were identified: MA&CS Experts (n = 182), MA&CS Newbies (n = 95), and Non-Athletes (n = 90). Among MA&CS Experts were more women [χ2(2) = 14.55, p < 0.001], older participants [H(2) = 236.42, p < 0.001], more experienced [H(2) = 8.31, p = 0.004], those with higher education [χ2(10) = 572.93, p < 0.001] and economic status [χ2(8) = 60.67, p < 0.001], and lower aggression scores [F(2, 161) = 10.443, p < 0.001], compared to MA&CS Newbies. MA&CS Newbies had higher physical aggression than Non-Athletes (p < 0.001). BJJ was overrepresented in the MA&CS Experts class, while KK and MMA were underrepresented [χ2(8) = 396.69, p < 0.001]. The MA&CS Newbies included athletes representing all four MA&CS disciplines in a similar proportion. The results highlight the role of long-term MA&CS training in potentially reducing aggression, particularly hostility, physical aggression, and verbal aggression. Demographic factors like age, gender, education, and economic status were also important in distinguishing the latent classes. The findings suggest aggression in MA&CS is a complex phenomenon influenced by multiple socio-cultural factors. Both the type of MA&CS and socio-demographic factors should be controlled by researchers and sports coaches if the goal of training is to reduce aggression in martial arts athletes.